2018
DOI: 10.1155/2018/8431249
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Protein Kinase C Isoforms Involved in Type 1 Diabetic Encephalopathy in Mice

Abstract: Diabetic encephalopathy is a complication of diabetes mellitus characterized by impaired cognitive functions. Protein kinase C (PKC) isoforms are rarely reported on diabetic encephalopathy, although they have been believed to play crucial roles in other diabetic complications. In this study, streptozotocin- (STZ-) induced diabetic mice were found to exhibit learning and memory deficits in the Morris water maze test. Meanwhile, the expression of cPKCβII, nPKCε, and cPKCγ did not change in the hippocampus, corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
(51 reference statements)
0
5
0
1
Order By: Relevance
“…Body weight and water and food intake were recorded once a week, and fasting blood glucose levels was assessed every 2 weeks from a tail vein blood sample using a OneTouch® Ultra blood glucose meter. Mice with blood glucose levels >11.1 mmol/L were selected as the diabetes model group for subsequent experiments [38]. In the present study, 26 diabetes model mice were obtained (26 of 32, 81.25%) and used for subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Body weight and water and food intake were recorded once a week, and fasting blood glucose levels was assessed every 2 weeks from a tail vein blood sample using a OneTouch® Ultra blood glucose meter. Mice with blood glucose levels >11.1 mmol/L were selected as the diabetes model group for subsequent experiments [38]. In the present study, 26 diabetes model mice were obtained (26 of 32, 81.25%) and used for subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
“… 29 The membrane translocation levels of cPKCγ have been shown to decrease in the cortex and striatum of mice with diabetic encephalopathy. 19 In this study, we found that the levels of cPKCγ membrane translocation increased after MD, and neuron numbers did not change significantly in the deprived visual cortex, suggesting that increased cPKCγ activation levels were not induced by neuron numbers.…”
Section: Discussionmentioning
confidence: 50%
“…The mouse visual cortex was dissected and rapidly frozen in liquid nitrogen. Based on our previous work, 18 , 19 frozen samples were thawed and homogenized in Buffer A (50-mM Tris-Cl, pH 7.5; 1-mM EGTA; 2 mM-EDTA; 100-µM sodium vanadate; 50-nM okadaic acid; 50-mM potassium fluoride; 5-mM sodium pyrophosphate; and 5 µg/µL each of pepstatin A, chymostatin, leupeptin, and aprotinin). Homogenates were then centrifuged at 100,000 g for 30 minutes at 4°C, and the supernatants were collected as the cytosolic fraction.…”
Section: Methodsmentioning
confidence: 99%
“…The organ indexes (organ weight/body weight) were statistically analyzed. According to the FBG values [ 22 , 23 ], the mice were divided into three groups as follows: control group (without ALX exposure), tolerant group (ALX exposure, nondiabetic mice with an FBG < 11.1 mmol/L), and sensitive group (ALX exposure, diabetic mice with an FBG ≥ 11.1 mmol/L).…”
Section: Methodsmentioning
confidence: 99%